(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and blessings and peace be upon our master Muhammad and his family and companions. And after : This study came under the title (The concept of contravention and its authority between Alhanafis and the public), to shed light on the most important area of disagreement between the Hanafis and the public and to extract the fruit of the disagreement through jurisprudential applications. I concluded that fundamentalists consider the concept of contravention as a justification which should be considered in scientific authorship , people’s contracts, their anecdotal actions and all their dealings; because the people’s convention and idioms in this issue in expressing their intentions indicates that, otherwise it would be in vain to introduce the restriction in their custom, However, the disagreement occurred in invoking the concept of contravention in the texts of the Sharia to the first two sayings that the concept of contravention is not an argument in the texts of Sharia, to which the Hanafis went to those who agreed with them, and the second: the concept of the makhala is a legitimate argument except the concept of the title, and to it went the majority of the fundamentalists from the Maliki and Shafi’i and the Hanbalis, but the public restricted their authority to eight conditions.